Examining The Spark of Reprehensible Factors in The Conception of The Unitary State - Jatmiko, Bayu Dwi Widdy; Safa’at, Rachmad; SN, Tunggul Anshari; Madjid, Abdul (Universitas Muhammadiyah Malang, 2024)
This article seeks to examine how the regulation of terrorism as a reprehensible act within the scope of special criminal acts in the National Criminal Code and its potential danger to Indonesia's existence as a unitary state. This research is normative juridical research, which uses conceptual and statute approaches based on primary and secondary legal materials obtained through library research. Then, the results are discussed using qualitative prescriptive analysis. The results obtained turned out to show that the regulation of terrorism as a despicable act within the scope of special crimes in the National Criminal Code intended to reinforce counterterrorism and radicalism efforts by including it as one of the special crimes by considering special characteristics. In addition, criminal acts of terrorism also have the potential to endanger the existence and sustainability of the Indonesian state as a welfare state; for that, there is a need for synergy in the role of the government and the people in the state.